1998
DOI: 10.1021/jp9829748
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the “Cold Fusion” of Bilayer Membranes

Abstract: Polymerization of the lipid headgroups inhibits calcium-induced fusion of small unilamellar vesicles of the lipid di-n-dodecyloxypropyl beta-nitrostyryl phosphate but does not influence vesicle aggregation. Addition of a copolymer of lauryl methacrylate and acrylamide (LMPAM) provides the vesicles with a steric shield that prevents both fusion and aggregation. Accurate microcalorimetric determination of the enthalpies of vesicle aggregation and fusion was possible by comparison of titrations of vesicles into C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 29 publications
0
23
0
Order By: Relevance
“…In the past few decades, the aggregation of vesicles has attracted special attention not only for its close relations to these biological processes as the analogous model, 3,4 but also for its practical importance in pharmacy and so on. [5][6][7] Normally, vesicle aggregation is induced by external additives. Salt-induced and polymerinduced vesicle aggregations have been well-investigated in numerous papers.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, the aggregation of vesicles has attracted special attention not only for its close relations to these biological processes as the analogous model, 3,4 but also for its practical importance in pharmacy and so on. [5][6][7] Normally, vesicle aggregation is induced by external additives. Salt-induced and polymerinduced vesicle aggregations have been well-investigated in numerous papers.…”
Section: Introductionmentioning
confidence: 99%
“…The amphiphilic compounds DDPBNS and DHPBNS are members of a family of synthetic lipids that provides a useful membrane mimetic system (Ravoo et al, 1996(Ravoo et al, , 1998(Ravoo et al, , 1999(Ravoo et al, , 2000. The molecular structures of DDPBNS and DHPBNS are presented in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we observed a very small positive enthalpy for calcium-induced lipid bilayer merging (0.15-0.25 kJ/mol lipid for the C12 analogue of DHPBNS (Ravoo et al, 1998). Fusion of Sendai virus with DHPBNS vesicles is endothermic by about 1.5 kJ/mol viral lipid.…”
Section: Discussionmentioning
confidence: 83%
“…We have recently reported that calcium-induced fusion of small vesicles is endothermic by 0.15 ± 0.10 kJ/mol lipid and driven by a gain in entropy of both lipid and water molecules as a result of bilayer merging (Ravoo et al, 1998). On the other hand, fusion of influenza virus and liposomes is endothermic by 2.5-2.9 kJ/mol viral lipid (Nebel et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation